2008
DOI: 10.1002/jcu.20495
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous unilateral dizygotic twin tubal pregnancy

Abstract: Spontaneous dizygotic unilateral twin tubal pregnancy is an extremely rare occurrence with a high risk for pregnancy-related mortality, and a diagnostic challenge for obstetricians. We present a case of a 27-year-old woman with spontaneous twin tubal pregnancy. Transvaginal color Doppler sonography revealed 2 separate gestational sacs within the right adnexa, each containing an embryo. Cytogenetic examination of the trophoblastic tissues confirmed the diagnosis of dizygotic twin ectopic pregnancy. Clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Such an event might be life-threatening for the patient if it is not treated on time and the patient can present with syncope and signs of shock includes tachycardia, pallor, and collapse. There may be abdominal distension and marked tenderness [3]. Although the incidence of ectopic pregnancy is only 1% of total pregnancies that have been reported, it is considered to be a major hazard for maternal health [4].…”
Section: Discussionmentioning
confidence: 99%
“…Such an event might be life-threatening for the patient if it is not treated on time and the patient can present with syncope and signs of shock includes tachycardia, pallor, and collapse. There may be abdominal distension and marked tenderness [3]. Although the incidence of ectopic pregnancy is only 1% of total pregnancies that have been reported, it is considered to be a major hazard for maternal health [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the incidence of tubal rupture in was about 32% and the risk of rupture rises about 2.5% for every 24 h period when untreated [19]. Until date, the surgical approach is the most reported option in literature to treat the unilateral tubal twin pregnancies [20]. There have been 4 cases of tubal twin pregnancies (3 unilateral, 1 bilateral) that methotrexate treatment has been tried [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Salpingostomy is preferred, particularly for women who wish to preserve their fertility. Twin ectopic pregnancy is usually treated surgically (9,16). When laparoscopic management is feasible, it is the preferred modality (17).…”
Section: Discussionmentioning
confidence: 99%